On a second‐order expansion of the truncated singular subspace decomposition. Issue 3 (25th January 2016) - Gratton, S.; Tshimanga‐Ilunga, J.
SUMMARY: We present a second‐order expansion for singular subspace decomposition in the context of real matrices. Furthermore, we show that, when some particular assumptions are considered, the obtained results reduce to existing ones. Some numerical examples are provided to confirm the theoretical developments of this study. Copyright © 2016 John Wiley & Sons, Ltd.